(untitled) (Agrikan Jurnal Agribisnis Perikanan, 2022)
Leaf development, plant height, branch formation, and tendrils of the telang plant (Clitoria ternatea) can be increased by applying organic fertilizer of butterfly pea (pea compost fertilizer, liquid organic fertilizer of pea, green pea fertilizer). Information related to the type of organic fertilizer that uses litter from the butterflypea plant and the accuracy of its application is not yet known so that this becomes the basis for research. The purpose of the research was to find out the interaction between types of organic pea fertilizers with the right interval of application. This research is an experimental research using a Randomized Block Design with 2 factors (factorial) and 4 replications, there are 9 treatment combinations and 36 experimental units. Parameters observed were number of leaves, plant height, number of branches and number of tendrils. Observational data were analyzed using variance and followed by the 5% Least Significant Difference (LSD) test. The results showed that the single factor of liquid organic fertilizer of pea gave the best results on the number of leaves, plant height and number of tendrils, also a single factor of 3 times fertilizer interval gave the best results on the number of leaves, number of branches, and number of tendrils. In addition, the interaction of liquid organic fertilizer with intervals of 3 times is the best type of treatment in increasing the growth of butterfly pea plant height.